An Original Field Experiment for Positioning of the Seafloor Acoustic Beacon Based on the Ranging Measurement from Surface-Navigation AUV - Anran Li; Fan Gao; Zhenqiang Song; Yuqing Li; Junhao Yang; Tianhe Xu; Honglei Ma (Marine Geodesy, 2026)

De novo transcriptome profiling reveals the bioeffect of the clam (Cyclina sinensis) to graded extremely low-frequency electromagnetic fields (ELF-EMF, 50 Hz) exposure - Mingming Zhang; Yuqing Fan; Mingfeng Zhu; Shouhai Liu; Hu Zhang; Chaojun Gu; Zhenyu Wang; Boping Yang; Guo Qiao (Environmental Pollution, 2026)

Triboelectric-motorized electromagnetic conversion enables frequency upconversion and impedance reduction for low-frequency mechanical energy harvesting - Tingyu Wang; Lihua Wang; Ai Chen; Bocheng Chen; Liming Tan; Junyin Cheng; Fan Xu; Huiyuan Wu; Kaixian Li; Yilan Zhang; Yuqing Wen; Haixuan Gan; et al. (Chemical Engineering Journal, 2026)

Muscle Organoids Frontier: Construction Strategies and Applications of Multi-lineage Muscle Organoids and Multi-organoid Systems - Dingding Wang; Lining Xu; Weijia Liu; Zitong Xie; Yuqing Sun; Mingxing Fan; Ling Wang; Quanzhong Ren; Yajun Liu; Junbo Liang; Renxian Wang (Phenomics, 2026)

Mechanism-based assessment of respirable dust exposure in miners: Integrating CFD-DPM simulation with personalized monitoring for occupational health risk - Jiajun An; Fan Geng; Yuqing Feng; Changgeng Gui; Shihang Li; Xinjian He; Guang Xu; Zheng Zhang; Yibao Wang (Journal of Environmental Chemical Engineering, 2026)

Polymerizable monomer for selective PFAS capture via fluorophilic interaction and cavity recognition: Rational design and applications in removal and sensing - Kun Zhang; Xiaonan Feng; Chuanzi Gao; Yulong Ma; Yuqing Dai; Zheqian Chen; Zhimin Fan; Xiaoyuan Guo; Tianhao Yang; Shangqing Wang; Mingdi Xu; Bintian Zhang (Chemical Engineering Journal, 2026)

Parental DEHP exposure induces sex-specific reproductive toxicity in zebrafish and behavioral deficits in unexposed offspring - Yanan Sun; Yuqing Fan; Yao Dang; Ping Ding; Xin Li; Gang Li; Haojie Luo; Jianliang Zhao; Guocheng Hu (Environmental Pollution, 2026)

Distribution, source, and pollution risk assessment of heavy metals in the coastal sediments of the northern South China sea - Wen Yu; Yuqing Fan; Qinghua Chen; Jing Yang; Xin Li; Wei Huang; Kun Yue; Liuyi Zhang; Ping Ding; Guocheng Hu; Yunjiang Yu (Environmental Pollution, 2026)

The response mechanisms of bacteria and microalgae to electrical stimulation in electro-assisted bacterial-algal system for mariculture wastewater treatment - Xiangrong Liu; Dongxu Xing; Hutao Wang; Yuqing Fan; Chunji Jin; Yangguo Zhao; Mengchun Gao; Liang Guo (Process Safety and Environmental Protection, 2026)

Efficient depolymerization of polystyrene waste into styrene monomers over the microwave-assisted Zn/b-ZnO catalyst system - Zijian Zhang; Bonan Liu; Li Yang; Jingwen Wang; Yuqing Dong; Chao Tang; Ping Wang; Haijiao Xie; Lei Zhang; Lu Zhang; Jun Zhao; Yu Fan; et al. (Journal of Environmental Chemical Engineering, 2026)

Establishment and optimisation of a transient transformation system for Taxus × media - Yang Menglu; Du Yuqing; Xu Fan; Wu Chenwei; Xia Siyu; Fan wei; Liu Shuai; Qiu Deyou; Yang Yanfang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

PVA modification mitigates PVDF hydrophobicity for concurrent protein and glycan analysis - Gang Liu; Yuqing Li; Yating Wang; Ning Fan; Zhi Li; Weijie Dong (Analytica Chimica Acta, 2026)

Effects of Hesperidin on the Intestinal Histological Structure, Goblet Cells, Tight Junction Proteins, and Nickel (NiCl2)-Induced Oxidative Stress - Jinquan Chen; Xinmei Fan; Juan Chen; Zhiqiao Pu; Xinyu Zhou; Xinqi Liu; Xuan Zhou; Yuqing Jiao; Ruiqing Wang; Mengya Ji; Mengyuan Zhang; Bangyuan Wu (Biological Trace Element Research, 2026)

A GPU-accelerated stiff ODE solver for combustion CFD with fully analytical chemical kinetics and heterogeneous CPU/GPU integration - Yuqing Cai; Yangyang Ban; Guanlin Dang; Tao Gong; Hu Wang; Fan Zhang; Zhi X. Chen (Fuel, 2026)

Coupled control mechanism of CO2 adsorption-phase density and occurrence model of CO2 in coal - Huihu Liu; Junlin Liu; Jinghao Yang; Zhengpu Fan; Hai Ding; Deyi Gao; Hongje Xu; Huihuang Fang; Kun Zhang; Yuqing Zhao (Fuel, 2026)

Effects of two-stage illumination strategy on the growth and nutrient composition of Chlorella sp. - Zhujun Qiu; Yuande Zhang; Yuqing Wang; Wenyu Zhao; Chonghui Fan; Yao Zhang; Ziyi Sun; Na Li; Qian Zhang (Algal Research, 2026)

Real-world aged microplastics exacerbate antibiotic resistance genes dissemination in anaerobic sludge digestion via enhancing microbial metabolite communication-driven pilus conjugative transfer - Tao Liu; Lipin Li; Junjie Chen; Guiyuan Cai; Fan Meng; Yimeng Jiao; Yuqing Mao; Zifan Wang; Wei Zuo; Yu Tian; Huihang Sun (Water Research, 2026)

Variations of stable carbon isotope imply sources of DIC in an alpine catchment - Meizhuang Zhu; Xingxing Kuang; Yuqing Feng; Enze Ma; Chunlin Song; Zhaoyong Hu; Xiaoyan Shi; Linfeng Fan; Fang Ji; Tian Zhao; Nima Ci Ren; Chunmiao Zheng (Journal of Hydrology, 2026)

Roasting oat-based paste modulates postprandial glucose and insulin sensitivity: Roles of acrylamide, texture, and starch fractions - Jiahui Hu; Zhihong Fan; Jinjie Wei; Xiyihe Peng; Qianqian Zhu; Rui Liu; Xinling Lou; Yuqing Xing (Food Research International, 2026)

Preparation of acetamiprid monoclonal antibody and its application in colorimetric and photothermal dual-mode immunochromatographic assay based on cu-doped PDA composite - Zixin Jin; Yuqing Yang; Hongyu Shi; Zhiwei Liu; Dongmei Bai; Ziwuzhen Wang; Caixu Fan; Yamin Liu; Qiuyue Ji; Wei Sheng; Shuo Wang (Food Chemistry, 2026)

Perillaldehyde controls citrus green mold by inhibiting the ribosome biogenesis of Penicillium digitatum and improving citrus disease resistance - Shuqi Liu; Yuxin Jiang; Jiancheng Sun; Fan Yang; Yuqing Wang; Yongqing Lu; Weiqiang Lai; Chao-an Long (Food Control, 2026)

UVA-LED365 nm and UVC-LED275 nm combined irradiation effectively inactivates Vibrio parahaemolyticus and controls photoreactivation by regulating illumination - Wenyu Zhao; Weixiao Zhang; Zhujun Qiu; Yuqing Wang; Chonghui Fan; Yao Zhang; Mingyuan Liu; Zhongliang Gao; Zi Liang; Ziyi Sun; Qian Zhang (Aquacultural Engineering, 2026)

Distribution patterns of potentially toxic elements in rhizosphere and non-rhizosphere soils of dominant plant species in the Yellow River Delta - Siqi Tong; Yuqing Fan; Yali Yang; Yanfeng Shi; Ming Li; Ruonan Wang; Xiaohui Liu; Bin Zhao (Environmental Monitoring and Assessment, 2025)

The probiotic characteristics and antimicrobial mechanisms of Lactiplantibacillus plantarum ZFM55 - Shiying Wu; Jiayi Fan; Yi Xu; Yuenuo Luo; Luying Xie; Mingyang Hu; Yongqiang Chen; Fangtong Wei; Yuqing Lou; Ping Li; Qing Gu (Food Bioscience, 2025)

Maillard reaction upgrades silver carp hydrolysates into prebiotic with immunomodulatory potential: The synergistic effects on immune function and gut microenvironment - Peipei Dou; Tianzhuo Huang; Hongbing Fan; Kai Wang; Xin Xiong; Xinxin Ren; Ruifang Feng; Yuqing Tan; Hui Hong; Yongkang Luo (Food Bioscience, 2025)

A cardiac-targeted nanozyme ameliorates myocardial infarction via antioxidation and regulation of MAPK signaling pathway - Jiahui Wang; Wei Meng; Qiujie Luo; Chenyang Wang; Haomiao Fan; Xiang Zhang; Shunbo Wei; Mengjie Hu; Xiaobo Yu; Yuqing Zhang; Binhao Zhang; Shuang Wang; et al. (Chemical Engineering Journal, 2025)

Real-time food freshness monitoring with AI assisted colorimetric and fluorescent dual-mode paper-based sensors: Harnessing size-dependent effects of mesoporous Cu2O - Zixin Jin; Zhiwei Liu; Ziwuzhen Wang; Yuqing Yang; Hongyu Shi; Caixu Fan; Yamin Liu; Qiuyue Ji; Wei Sheng; Long Ma; Shuo Wang (Chemical Engineering Journal, 2025)

Synthesis of cellulose derivatives bearing regioselective bulky thiazolyl substituents at 2,3- and 6-positions for efficient fluorescence and UV–visible detection of Cu2+/Fe3+ ions - Fan Wang; Yuqing Wang; Lili Zhang; Ting Zheng; Jun Shen (Carbohydrate Polymers, 2025)

Serum Metabolome Profiling Reveals Biomarkers to Predict Malignant Brain Edema Following Endovascular Stroke Therapy - Jiaqi Luo; Xiaolin Zhao; Mengxuan Xiao; Junlin Deng; Shuhua Xie; Huanhuan Fan; Wenting Lu; Yuqing Su; Tong Wu; Huanrong Ma; Xianghong Liu; Suyue Pan; et al. (Translational Stroke Research, 2025)

Synergistic effects of nutrient competition, biotic interactions, and hydrological regulation drive green tide outbreaks in the South Yellow Sea - Guanbing Feng; Jingfei Liu; Ning Wang; Lihua Xia; Jiahao Fan; Qingqing Mu; Yuqing Sun; Peiming He; Jianheng Zhang (Harmful Algae, 2025)

Life-history-dependent and seasonally varying distribution patterns of Atlantic bigeye (Priacanthus arenatus) in western African coast - Fengyuan Shen; Yuqing Zhang; Chunlei Feng; Taichun Qu; Ruiliang Fan; Zhixuan Feng; Hanfeng Zheng; Hui Xu; Hewei Liu; Shuai Li; Xiumei Fan; Xue Wang; et al. (Frontiers in Marine Science, 2025)
Understanding spatiotemporal distribution patterns of fish across life history stages is critical for sustainable fishery management, particularly in data-poor regions such as the extensive yet poorly explored western African coastal regions. This study investigates the distribution patterns and ontogenetic habitat shifts of Atlantic bigeye ( Priacanthus arenatus ) at various life stages on the coast of Sierra Leone using data from twelve cruises conducted between 2019 and 2021. Our results reveal distinct life-stage partitioning across multiple life stages of Atlantic bigeye. Juveniles (<60 mm body length) predominantly distribute in the pelagic waters beyond the continental shelf. As individuals reach a body length of approximately 60 mm, they enter the sub-adult stage, characterized by the onset of gonad development and a noticeable migration to demersal areas within the continental shelf. Adults (≥150 mm body length) are basically demersal as populations primarily distribute in demersal areas within the continental shelf. Our observations also suggest that juvenile Atlantic bigeye exhibits capture peaks: one prior to the rainy season (April–May) and the other after the rainy season (September–October), suggesting a potential correlation with spawning. Moreover, the extensive offshore distribution of juveniles beyond the continental shelf appears to be closely associated with seasonal river plume spread, potentially reflecting a behavioral adaptation to utilize oceanic dispersal pathways during periods of enhanced freshwater input. These findings fill a critical knowledge gap and provide a scientific basis for fisheries research and management of this species in western African waters.

Spatio-temporal dynamics of L-band zeroth-order vegetation scattering albedo from SMAP observations in tropical forests - Yuqing Liu; Xiaojun Li; Philippe Ciais; Frédéric Frappart; Xiangzhuo Liu; Eric G. Cosio; Yi Zheng; Zanpin Xing; Huan Wang; Lei Fan; Mario Julian Chaubell; Jean-Pierre Wigneron (Remote Sensing of Environment, 2025)

Corrigendum to “Microplastic characteristics and their potential ecological risks to Auxis thazard and Symplectoteuthis oualaniensis in the Indian Ocean” [Mar. Environ. Res. 210(2025) 107304] - Zhenghao Wang; Menghong Hu; Sijie Fan; Hanfeng Zheng; Cuihua Wang; Manzoor Ahmad; Lingzhi Li; Guoqing Zhao; Gangchen Zhang; Yuqing Zhang; Jianwei Hu; Youji Wang (Marine Environmental Research, 2025)

Dual network CMCS/PNIPAM temperature-sensitive hydrogel based fluorescent and RGB colorimetric dual-mode immunosensor for detection of capsaicinoids as an exogenous index in edible oil samples - Ziwuzhen Wang; Wei Sheng; Zixin Jin; Hongyu Shi; Zhiwei Liu; Yuqing Yang; Shuo Wang; Qiuyue Ji; Caixu Fan; Yamin Liu (Chemical Engineering Journal, 2025)

Transcriptome profiling of fruits at different development stages in the Field Muskmelon (Cucumis melo L. var. agrestis Naud.) “Mapao 1” - Yupeng Fan; Yuqing Zhou; Yushu Yuan; Runzhe Xu; Xiuxiu Zhu; Yupeng Pan; Huijun Zhang (Plant Science, 2025)

Microplastic pollution in the Indian Ocean: Fiber-dominated contamination and comparative bioaccumulation in Auxis thazard and Symplectoteuthis oualaniensis - Zhenghao Wang; Menghong Hu; Jiesi Fan; Hanfeng Zheng; Cuihua Wang; Manzoor Ahmad; Lingzhi Li; Guoqing Zhao; Gangchen Zhang; Yuqing Zhang; Jianwei Hu; Youji Wang (Marine Environmental Research, 2025)

Spectral ultra-stable perovskite quantum dots for pure-blue light-emitting diodes - Zhixuan Lu; Yuqing Li; Lulu Wei; Yi Jiang; Furong Yu; Huan Fan; Jinxin Yang; Jun Xing; Zhanhua Wei (Chemical Engineering Journal, 2025)

Distribution characteristics and risk assessment of hexabromocyclododecanes in soil from e-waste dismantling areas - Jun Pan; Ping Ding; Jiaji Zhang; Chushan Huang; Lijuan Zhang; Wei Huang; Yuqing Fan; Guocheng Hu (Environmental Geochemistry and Health, 2025)

Maillard reaction enhances prebiotic potential of silver carp hydrolysates: Insights from SCFA production, microbiome, and metabolomics - Peipei Dou; Huijuan Zhang; Ning Ding; Elliot Mubango; Hongbing Fan; Ce Shi; Hui Hong; Yuqing Tan; Yongkang Luo (Food Bioscience, 2025)

Prediction of multi-task physicochemical indices based on hyperspectral imaging and analysis of the relationship between physicochemical composition and sensory quality of tea - Xinna Jiang; Xingda Cao; Quancheng Liu; Fan Wang; Shuxiang Fan; Lei Yan; Yuqing Wei; Yun Chen; Guijun Yang; Bo Xu; Quan Wu; Ze Xu; et al. (Food Research International, 2025)

Ginsenoside Rk1 Ameliorates Non-Alcoholic Fatty Liver Disease by Targeting CD36 to Modulate the AMPK Signaling Pathway - Yuqing Wu; Zhiguang Duan; Linlin Qu; Yannan Liu; Xiaoxuan Ma; Daidi Fan (Food Research International, 2025)

A steel plate-coarse aggregate UHPC composite joint equivalent to cast-in-place in the negative moment regions - Kaiwei Lu; Yuqing Tan; Kangkang Wang; Fan Zhang; Jingquan Wang (Engineering Structures, 2025)

Effect of Molecular Weight of Fluorescent Dyes on DNA Separation by Capillary Electrophoresis - Yuqing Xu; Xin Chen; Shuaiqiang Fan; Ting Zhang; Bo Yang; Zhenqing Li; Shintaro Yamaguchi; Dawei Zhang (Journal of Fluorescence, 2025)

Effects of tebuconazole on insecticidal activity and symbionts in brown planthopper, Nilaparvata lugens (Hemiptera: Delphacidae) - Yuqing Zhong; Qian Wang; Fan Sun; Xiaoping Yu; Yipeng Liu; Xuping Shentu (Pesticide Biochemistry and Physiology, 2025)

Evaluation and process monitoring of jujube hot air drying using hyperspectral imaging technology and deep learning for quality parameters - Quancheng Liu; Xinna Jiang; Fan Wang; Shuxiang Fan; Baoqing Zhu; Lei Yan; Yun Chen; Yuqing Wei; Wanqiang Chen (Food Chemistry, 2025)

Occurrence of Volatile Organic Compounds and Associated Risk Assessments in Dongting Lake, China - Ruonan Wang; Liyuan Yang; Yuqing Fan; Shichao Ma; Siqi Tong; Xiaochun Guo; Shaoyong Lu (Water, Air, & Soil Pollution, 2025)

Biochar supported modified nZVI for effective remediation of hexavalent chromium: Enhanced performance and remediation mechanism - Chuanyu Li; Ye Hu; Chao Yan; Yuqing Zhang; Yuxian Fan; Debin Ji; Baohui Wang; Lingyue Zhu (Journal of Environmental Chemical Engineering, 2024)

How the landscape pattern and landscape elements affect the source-based soundscape diversity - Weicong Fu; Jingkai Huang; Chengyu Ran; Wenqiang Fang; Shiyuan Fan; Yujie Zhao; Peilin Huang; Ziluo Huang; Jiaying Dong; Yuqing Huang; Ziru Chen (Urban Ecosystems, 2024)

Multiple NADPH-cytochrome P450 reductases from Lycoris radiata involved in Amaryllidaceae alkaloids biosynthesis - Yuqing Wu; Yifeng Zhang; Haitong Fan; Jie Gao; Siyu Shen; Jifan Jia; Rong Liu; Ping Su; Yating Hu; Wei Gao; Dan Li (Plant Molecular Biology, 2024)

Interaction regimes of surface water and groundwater in a hyper-arid endorheic watershed on Tibetan Plateau: Insights from multi-proxy data - Yong Xiao; Yuqing Zhang; Hongjie Yang; Liwei Wang; Jibin Han; Qichen Hao; Jie Wang; Zhen Zhao; Wenxu Hu; Shengbin Wang; Qishun Fan; Zexue Qi (Journal of Hydrology, 2024)

Icariin-loaded selenium-gold multi-shell nanocomposites with NIR-II response release to relieve post-damaged bone microenvironment for osteoporosis synergy therapy - Yuqing Li; Xiaotong Feng; Yuwei Li; Qile Song; Naling Long; Xiaoting Fu; Yifan Wang; Yingjiao He; Huiying Yan; Cong Li; Lina Feng; Cundong Fan; et al. (Chemical Engineering Journal, 2024)

Deep learning models with optimized fluorescence spectroscopy to advance freshness of rainbow trout predicting under nonisothermal storage conditions - Yanwei Fan; Ruize Dong; Yongkang Luo; Yuqing Tan; Hui Hong; Zengtao Ji; Ce Shi (Food Chemistry, 2024)

Inventorization and ecological risk assessment of tetrabromobisphenol A and hexabromocyclododecane in sediments from Guangdong coastal area of South China Sea - Xiaoxia Chen; Xin Li; Yuqing Fan; Guocheng Hu; Hang Xie; Xiaoyan Chen; Ping Ding; Yao Dang; Xiyuan Hu; Qinghua Chen (Science of The Total Environment, 2024)

Microwave-induced thermal response and protein variation of oil-water biphasic systems in foods: A Case study of anhydrous butter and skim milk - Yuqing Tao; Yuan Tao; Huayu Yang; Bowen Yan; Nana Zhang; Yan Zhang; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Journal of Food Engineering, 2024)

Soil quality and ecosystem multifunctionality after 13-year of organic and nitrogen fertilization - Chunli Wang; Yuqing Ma; Wenhai He; Yakov Kuzyakov; Roland Bol; Haiqing Chen; Mingsheng Fan (Science of The Total Environment, 2024)

Postharvest biocontrol ability and antagonistic mechanism of Bacillus altitudins h217 against Penicillium digitatum in citrus - Yongqing Lu; Shuqi Liu; Yuqing Wang; Fan Yang; Zhonghuan Tian; Chao-an Long (Postharvest Biology and Technology, 2024)

Effects of imidacloprid combined with validamycin on the population fitness and symbiotic of Nilaparvata lugens (Hemiptera: Delphacidae) - Yipeng Liu; Fan Sun; Yuqing Zhong; Qian Wang; Xiaoping Yu; Xuping Shentu (Pesticide Biochemistry and Physiology, 2024)

Utilizing ragweed and oyster shell derived biochar as an effective stabilizer for the restoring Cd and Pb- contaminated soil - Xueliu Gong; Wanli Lian; Shuai Tian; Qiuyu Yu; Zilin Guo; Xin Zhang; Yuan Yuan; Yuqing Fan; Zhiwei Liu; Jufeng Zheng; Rongjun Bian; Lianqing Li; et al. (Geoderma Regional, 2024)

Effects of endoplasmic reticulum stress on chondrocyte apoptosis via the PI3K/AKT signaling pathway - Libo Zhou; Fan Wu; Jing Wang; Yuqing Zhao; Gaoyi Wu; Yucheng Su (Tissue and Cell, 2024)

Efficient removal of Cd(II) and Pb(II) from aqueous solution using biochars derived from food waste - Shuai Tian; Xueliu Gong; Qiuyu Yu; Fei Yao; Wenjian Li; Zilin Guo; Xin Zhang; Yuan Yuan; Yuqing Fan; Rongjun Bian; Yan Wang; Xuhui Zhang; et al. (Environmental Science and Pollution Research, 2023)

Cellulose/amylose derivatives bearing bulky substituents as reversible fluorescent sensors for detection of Fe3+ - Fan Wang; Weiqi Wang; Yuqing Wang; Lili Zhang; Yoshio Okamoto; Jun Shen (Carbohydrate Polymers, 2023)

Coating CoFe2O4 shell on Fe particles to increase the utilization efficiencies of Fe and peroxymonosulfate for low-cost Fenton-like reactions - Yuqing Sun; Chengbo Ma; Di Wu; Xiaomei Liu; Ning Li; Xiaobin Fan; Yang Li; Guoliang Zhang; Fengbao Zhang; Wenchao Peng (Water Research, 2023)

Curcumin-activated Olfactory Ensheathing Cells Improve Functional Recovery After Spinal Cord Injury by Modulating Microglia Polarization Through APOE/TREM2/NF-κB Signaling Pathway - Chao Jiang; Zhe Chen; Xiaohui Wang; Yongyuan Zhang; Xinyu Guo; Hong Fan; Dageng Huang; Yuqing He; Xiangwen Tang; Yixiang Ai; Youjun Liu; Hao Yang; et al. (Journal of Neuroimmune Pharmacology, 2023)
Transplantation of curcumin-activated olfactory ensheathing cells (aOECs) improved functional recovery in spinal cord injury (SCI) rats. Nevertheless, little is known considering the underlying mechanisms. At the present study, we investigated the promotion of regeneration and functional recovery after transplantation of aOECs into rats with SCI and the possible underlying molecular mechanisms. Primary OECs were prepared from the olfactory bulb of rats, followed by treatment with 1µM CCM at 7–10 days of culture, resulting in cell activation. Concomitantly, rat SCI model was developed to evaluate the effects of transplantation of aOECs in vivo. Subsequently, microglia were isolated, stimulated with 100 ng/mL lipopolysaccharide (LPS) for 24 h to polarize to M1 phenotype and treated by aOECs conditional medium (aOECs-CM) and OECs conditional medium (OECs-CM), respectively. Changes in the expression of pro-inflammatory and anti-inflammatory phenotypic markers expression were detected using western blotting and immunofluorescence staining, respectively. Finally, a series of molecular biological experiments including knock-down of triggering receptor expressed on myeloid cells 2 (TREM2) and analysis of the level of apolipoprotein E (APOE) expression were performed to investigate the underlying mechanism of involvement of CCM-activated OECs in modulating microglia polarization, leading to neural regeneration and function recovery. CCM-activated OECs effectively attenuated deleterious inflammation by regulating microglia polarization from the pro-inflammatory (M1) to anti-inflammatory (M2) phenotype in SCI rats and facilitated functional recovery after SCI. In addition, microglial polarization to M2 elicited by aOECs-CM in LPS-induced microglia was effectively reversed when TREM2 expression was downregulated. More importantly, the in vitro findings indicated that aOECs-CM potentiating LPS-induced microglial polarization to M2 was partially mediated by the TREM2/nuclear factor kappa beta (NF-κB) signaling pathway. Besides, the expression of APOE significantly increased in CCM-treated OECs. CCM-activated OECs could alleviate inflammation after SCI by switching microglial polarization from M1 to M2, which was likely mediated by the APOE/TREM2/NF-κB pathway, and thus ameliorated neurological function. Therefore, the present finding is of paramount significance to enrich the understanding of underlying molecular mechanism of aOECs-based therapy and provide a novel therapeutic approach for treatment of SCI.

A highly selective and sensitive sensor for promethazine based on molecularly imprinted interface coated Au/Sn bimetal nanoclusters functionalized acupuncture needle microelectrode - Hongying Liu; Cairui Zhang; Chenwei Wang; Kai Fan; Yuqing Zhang; Lu Fang; Lihua Li; Chaoxiang Ren; Zheng-Zhi Yin; Zhong Lü (Analytica Chimica Acta, 2023)

Synthesis of amylose and cellulose derivatives bearing bulky pendants for high-efficient chiral fluorescent sensing - Fan Wang; Weiqi Wang; Yuqing Wang; Wei Zheng; Ting Zheng; Lili Zhang; Yoshio Okamoto; Jun Shen (Carbohydrate Polymers, 2023)

An uncoupled damping system for tension-only braced structures: experimental and numerical analysis - Zi Gu; Wensheng Lu; Yuan Fan; Yuqing Gao (Engineering Structures, 2023)

An Updated Review on Ag NP Effects at Organismal Level: Internalization, Responses, and Influencing Factors - Fan Mo; Haibo Li; Yuqing He; Qixing Zhou (Reviews of Environmental Contamination and Toxicology, 2022)

The impact of cross-shareholding under different power structures considering green investment and green marketing - Hao Liu; Sheng Wu; Xinyue Zhao; Haodong Chen; Guobao Wang; Zhigang Song; Yuqing Fan (Environmental Science and Pollution Research, 2022)

Transcriptomics and targeted metabolomics reveal the regulatory network of Lilium davidii var. unicolor during bulb dormancy release - Xinyue Fan; Yue Yang; Min Li; Linlan Fu; Yuqing Zang; Chunxia Wang; Tianyou Hao; Hongmei Sun (Planta, 2021)

Endoplasmic reticulum stress is involved in retinal injury induced by repeated transient spikes of intraocular pressure - Xue Yang; Xiaowei Yu; Zhenni Zhao; Yuqing He; Jiamin Zhang; Xiaoqian Su; Nannan Sun; Zhigang Fan (Journal of Zhejiang University-SCIENCE B, 2021)

Macrophage Polarization in Response to Biomaterials for Vascularization - Yuqing Wang; Yubo Fan; Haifeng Liu (Annals of Biomedical Engineering, 2021)

Assessing benthic habitat quality using biotic indices in the Laizhou Bay, China - Li Wang; Xianxiang Luo; Jianqiang Yang; Juan Zhang; Yuqing Fan; Jiayu Shen (Acta Oceanologica Sinica, 2020)

Benthic habitat quality assessment based on biological indices in Xiaoqing River estuary and its adjacent sea of Laizhou Bay, China - Xianxiang Luo; Song Lin; Jianqiang Yang; Jiayu Shen; Yuqing Fan; Longjun Zhang (Journal of Ocean University of China, 2017)

Aging with higher fractional exhaled nitric oxide levels are associated with increased urinary 8-oxo-7,8-dihydro-2′-deoxyguanosine concentrations in elder females - Jian Hou; Yuqing Yang; Xiji Huang; Yuanchao Song; Huizhen Sun; Jianshu Wang; Fan Hou; Chuanyao Liu; Weihong Chen; Jing Yuan (Environmental Science and Pollution Research, 2016)

Dispersal of the broad mite, Polyphagotarsonemus latus (Acari: Tarsonemidae) on Bemisia argentifolii (Homoptera: Aleyrodidae) - Yuqing Fan; Frederick L. Petitt (Experimental and Applied Acarology, 1998)